Optimalisasi Pengawasan Guru Dan Tenaga Kependidikan Melalui Pemanfaatan Website Linktree Pada Sub Bagian Tata Usaha Sekolah Menengah Kejuruan Negeri 2 Pelaihari Dinas Pendidikan Provinsi Kalimantan Selatan - Yulia Rahmi; Khuzaini; Syahrial Shaddiq (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
In the digital era, the utilization of information and communication technology (ICT) in education is crucial, especially in supervising Teachers and Education Personnel (GTK). This study aims to explore the optimization of GTK supervision at SMKN 2 Pelaihari, South Kalimantan, through the use of the Linktree website. The research method employed is descriptive qualitative, with data collection through literature study, observation, and interviews. The findings indicate that the use of Linktree can enhance administrative efficiency, information accessibility, transparency, and reduce the workload of administrative staff. Furthermore, this system has the potential to improve GTK performance and educational quality. Implementation is carried out through stakeholder consultation, system development, socialization, training, and monitoring and evaluation. This study provides recommendations for further development of the Linktree system to be more integrated and effective in educational administration management.